2020
DOI: 10.1111/acel.13254
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of resident notochord‐descendent nucleus pulposus cells in mouse injury‐induced fibrotic intervertebral discs

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Nonetheless, there are studies indicating that mouse NPs do become less cellular with ageing, as demonstrated in inbred SM/J mice [17] and genetically modified strains such as premature ‘disc degeneration’ in mice with notochord-specific deletion of Ccn2, conditionally deleted Sox9 in Acan -expressing cells, or caveolin-1 -null mice [66] , [67] , [68] . Further, in injury (IVD puncture) or mechanical-loading induced degeneration (tail looping) [67] mouse models for IDD, there is a loss of the vacuolated NLCs and a shift towards cells with chondrogenic and fibroblastic characteristics [26] , which is also observed in human discs in ageing and degeneration [7] , [8] . Thus, despite a comparable postnatal stage in terms of sexual maturity, the 8-week mouse and the 16yo human NPs are vastly different, and that the former may reflect a younger version of the latter.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nonetheless, there are studies indicating that mouse NPs do become less cellular with ageing, as demonstrated in inbred SM/J mice [17] and genetically modified strains such as premature ‘disc degeneration’ in mice with notochord-specific deletion of Ccn2, conditionally deleted Sox9 in Acan -expressing cells, or caveolin-1 -null mice [66] , [67] , [68] . Further, in injury (IVD puncture) or mechanical-loading induced degeneration (tail looping) [67] mouse models for IDD, there is a loss of the vacuolated NLCs and a shift towards cells with chondrogenic and fibroblastic characteristics [26] , which is also observed in human discs in ageing and degeneration [7] , [8] . Thus, despite a comparable postnatal stage in terms of sexual maturity, the 8-week mouse and the 16yo human NPs are vastly different, and that the former may reflect a younger version of the latter.…”
Section: Discussionmentioning
confidence: 95%
“…To achieve a comprehensive characterization of a “healthy” mouse IVD, we performed label-free deep proteomics (by LC-MS/MS; Methods and Supplementary materials ) on NP and AF of 8-week-old Foxa2 mNE -Cre/ZEG mice (on mixed C57BL/6J and B6CBAF1/J backgrounds) [26] , in which the NP are tagged by enhanced green fluorescent protein (eGFP). This was followed by systemic analyses and validation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and prevalence of LBP in China have increased annually, and it has become one of the major diseases that affect both public health and people’s quality of life ( Yao et al, 2011 ; Wu et al, 2019 ). Previous studies ( Liao et al, 2019a ; Au et al, 2020 ; Binch et al, 2021 ; Croft et al, 2021 ) showed that intervertebral disc (IVD) degeneration (IVDD) is the most prevalent contributor to LBP at present. Although the etiology of IVDD remains poorly understood, some influencing factors include metabolic disorders, aging, mechanical loading, trauma, infection, nutrition, and genetic predisposition ( Deyo and Weinstein, 2001 ; Cherif et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…MFs express alpha-smooth muscle actin (α-SMA) [ 21 ] and are responsible for extensive ECM deposition, namely collagen, within fibrotic tissue, altering tissue architecture and function [ 21 23 ]. In the IVD, upon injury, MFs have been suggested to be involved in the AF repair process [ 24 , 25 ]. The presence of α-SMA+ cells in IVD herniation has also been studied, being increased in degenerated and extruded IVDs, both in human and rat [ 12 ].…”
Section: Introductionmentioning
confidence: 99%